An Overview on the Mechanisms of Neuroprotection and Neurotoxicity of Isoflurane and Sevoflurane in Experimental Studies - Neag, Maria-Adriana; Mitre, Andrei-Otto; Catinean, Adrian; Mitre, Calin-Iosif (Brain research bulletin, 2020)
•Anaesthetics can be protective or toxic based on the brains age and pathology•The effects vary based on the neuronal development state and pathological background•New-borns and elderly subjects are the most vulnerable to anaesthetics toxicity•There are several inter-linked pathways that contribute to toxicity and protection•Neuronal effects seem to be more pronounced in male subjects Since their first use, anaesthetic agents have seen major advancements and are now an indispensable element of surgical procedures. Two of the most used volatile anaesthetics are isoflurane and sevoflurane. These have neuroprotective effects on adult brains in different brain disorders, ranging from traumatic to hypoxic or ischemia-reperfusion injuries. In new-borns and elderly patients these effects are reversed, and volatile anaesthetics might have a neurotoxic effect, affecting the recovery and neurological capabilities of these patients. Since we are still using volatile anaesthetics, it is important to know in which conditions these substances are neurotoxic and neuroprotective, as well as to better understand the mechanisms underlying these effects. In this review we aim to summarise the current knowledge on the mechanisms involved in neuroprotection and neurotoxicity of neonatal, adult and aged brains and how these vary based on the brains age and underlying pathologies. This review should guide future experimental research towards less studied mechanisms and should help the development of neuroprotective strategies. Also, we provide a short summary of the substances used in experimental studies to prevent the neurotoxic effect of isoflurane and sevoflurane.